(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article deals with the features of the narrative composition in Jaume Cabré’s novel «I Confess». It is revealed that the types of narration from the first and the third person are switched and alternated with a rather unusual type of narration from the second person point of view. The two main narrative lines are integrated with each other so that it is difficult to identify the boundaries within the texture. The composition of the narrative, which displays the corresponding world view of the protagonist, is based on the principle of asymmetric distribution of inserts. We can observe coexistence of the fragments with a predominantly homogeneous type of narrative from the third or first person with fragments in which there is an alternation of the narrative point of view within one paragraph. The oscillation between points of view allows the author to more closely control the emotional reaction of the reader and creates a very specific stylistic effect.